2022
DOI: 10.3390/ijerph19031258
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Agile Work Practices and Occupational Well-Being: The Role of Job Demands and Resources

Abstract: Agile work practices have been adopted by most software development organizations and by many large organizations from other industries. The introduction of agile work practices is assumed to positively affect work characteristics and, in turn, well-being of employees. So far, there is only very little and methodologically limited empirical research on this topic. Based on job demands–resources theory, we developed and tested a model on the direct and indirect relationships between agile work practices, job de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…Additionally, there is a multitude of other empirical Agile project management and creativity research showing a connection between agile work practices and occupational well-being. Recent research by Rietze and Zacher (2022) suggests that agile work practices reduce the risk of emotional fatigue and increase emotional engagement; the study seems to support "the assumption that agile work practices provide a framework for more humane, motivating, and fulfilling work" (p. 17). The use of agile methods can also reduce work exhaustion by lowering both role ambiguity and role conflict in software developers, as it was determined by Venkatesh et al (2020).…”
Section: Agile Project Management As a Space For Creativitymentioning
confidence: 69%
“…Additionally, there is a multitude of other empirical Agile project management and creativity research showing a connection between agile work practices and occupational well-being. Recent research by Rietze and Zacher (2022) suggests that agile work practices reduce the risk of emotional fatigue and increase emotional engagement; the study seems to support "the assumption that agile work practices provide a framework for more humane, motivating, and fulfilling work" (p. 17). The use of agile methods can also reduce work exhaustion by lowering both role ambiguity and role conflict in software developers, as it was determined by Venkatesh et al (2020).…”
Section: Agile Project Management As a Space For Creativitymentioning
confidence: 69%
“…In line with this, Mann and Maurer (2005) found that the amount of overtime decreased in projects that adopted an agile method as the new way of working and that the working mode shifted toward a more sustainable pace. Lastly, Rietze and Zacher (2022) found that agile work practices have a negative effect on emotional fatigue by lowering work demands and a positive effect on emotional engagement through higher job resources. As the current state of the literature is somewhat inconclusive, we will examine the relationship between workforce agility and well-being further in this research.…”
Section: Workforce Agility and Well-beingmentioning
confidence: 93%
“…Trépanier et al (2014) incorporate physical demands such as carrying objectives into the content of job demands. According to Rietze and Zacher (2022), time constraints and work interruptions are challenging aspects of job demands. The resources primarily present all positive and supportive aspects of the job to facilitate work completion (Demerouti et al, 2001;Trépanier et al, 2014), such as work-related materials, organisational support, social support, and personal positive resources.…”
Section: Job Demand-resource Theory Modelmentioning
confidence: 99%